Tourism Development Strategy Based on Intangible Cultural Heritage: JEL Classification: Z32, O21, R11, Z10 - Morena, Mochammad Rian Ahdian; Nurbaeti, Nurbaeti; Asmaniati, Fetty; Amrulah, Amrulah; Karo, Pelliyezer Karo (Newinera Publisher, 2025)
OKI Regency holds significant potential for developing tourism based on intangible cultural heritage. With diverse attractions of intangible cultural heritage, OKI offers a unique experience for tourists. Despite strengths in attractions and accessibility, Ancillary services, accommodation, and promotion improvements are needed. Strategic recommendations include community empowerment, infrastructure enhancement, effective promotion, and sustainable management. Implementing these suggestions can enhance OKI's allure as a destination for intangible cultural heritage tourism, providing economic benefits and ensuring destination sustainability. The SWOT analysis highlights cultural diversity and infrastructure as strengths, while insufficient promotion and coordination are weaknesses. Enhanced promotion through media and managing the risk of losing authenticity pose opportunities and threats. OKI has the potential to become a flagship destination, combining the richness of intangible cultural heritage in an enticing and sustainable tourism experience.